Pengaruh Tingkat Kesulitan Orang Tua Tunggal Terhadap Karakter Kemandirian Anak di Kelurahan Beringin Raya - Virda Septiani; Berchah Pitoewas; Rohman Rohman; Yunisca Nurmalisa; Elisa Seftriyana (Jurnal Pendidikan Sosial Dan Konseling, 2026)
This study aims to determine the effect of single parents' difficulties on children's independence character in Beringin Raya Village. The difficulties experienced by single parents include economic burdens, limited time, psychological stress, and low social support based on Reuben Hill's Family Stress Theory. Children's independence character is measured through emotional autonomy, behavioral autonomy, and value autonomy based on Laurence Steinberg's theory. This study employed a quantitative approach with a descriptive associative method. Data were collected through questionnaires, interviews, and documentation involving 53 single parents. Data analysis used normality tests, linearity tests, and simple linear regression with SPSS version 26. The results indicate that the level of difficulties experienced by single parents significantly affects children's independence character, with a significance value of 0.047 (<0.05). The regression coefficient of -0.252 indicates a negative relationship, meaning that the higher the level of difficulties experienced by single parents, the lower the children's independence character. These findings emphasize the importance of support from families, communities, and educational institutions in fostering children's independence.